Employment programming fuzzy goal in medical field - منفي صباح; حسن نورس عبد الكريم (Journal of Economics and Administrative Sciences, 2014)
The aim of this study is to use style programming goal and technical programming goal fuzzy to study assessing need annual accurately and correctly depending on the data and information about the quantity the actual use of medicines and medical supplies in all hospitals and health institutions during a certain period where they were taking the company public for the marketing of medicines and medical supplies sample for research. Programming model was built goal to this problem, which included (15) variable decision, (19) constraint and two objectives: 1 - rational exchange of budget allocated for medicines and supplies. 2 - ensure that the needs of patients of medicines and supplies needed to improve their health and raise the level of health of the citizens in general. Then a model using the software solution ready-win QSB that was reached using the programming technique fuzzy goal in determining the optimal quantities of medicines and medical supplies give the best results.